THE EFFECT OF COMPETENCY AND WORK FACILITIES ON NURSES' PERFORMANCE WITH JOB SATISFACTION AS AN INTERVENING VARIABLE AT PULANG PISAU REGIONAL PUBLIC HOSPITAL - Afrini Freine Freyle Wior; Surachmad, Surachmad (Sean Institute, 2021)
Performance as an embodiment of a nurse's work behavior that is displayed as work performance in accordance with its role in a hospital within a certain period. This indicates the performance of nurses as a determinant of the success and survival of the hospital. In every hospital, nurses are one of the most important components in reviving the hospital. This must be supported by good performance because without good performance, the hospital will not achieve its goals. For this reason, nurses need satisfaction to be able to work more diligently. To achieve good performance, competence and work facilities are very influential. In addition, the job satisfaction obtained by nurses is an important aspect, because it can have an impact on better performance. Therefore, this study aims to determine the effect of competence, work facilities and job satisfaction on the performance of nurses. The population in this study were all employees and nurses at the Pulang Pisau District Hospital, totaling 90 people. The researcher uses a saturated sampling technique, meaning that all populations can be used as samples in this study. The data analysis in this study used a path analysis model, because of the intervening variables in this research model. The results of this study indicate that competence and work facilities have a significant positive effect on job satisfaction. Competence, work facilities and job satisfaction are proven to have a significant positive effect on nurse performance.